Treatment Outcomes of 94 Cases of Pipeline Embolization Device in a Single Center: Predictive Factors of Incomplete Aneurysm Occlusion - Miyachi, Shigeru; Hiramatsu, Ryo; Furuse, Motomasa; Kameda, Masahiro; Kawabata, Shinji; Yagi, Ryokichi; Nonoguchi, Naosuke; Ohnishi, Hiroyuki; Wanibuchi, Masahiko (Journal of Neuroendovascular Therapy, 2023)
Objective: This study aimed to report the outcome of an endovascular treatment with a pipeline embolization device (PED) at a single center. We also examined the predictive factors for an incomplete occlusion after the PED placement.Methods: The subjects were 94 patients with 109 aneurysms who underwent the PED placement at our single center from June 2015 to September 2022. As treatment outcomes, we investigated the PED placement success rate, perioperative morbidity and mortality, postoperative cranial nerve improvement rate, and the classification of angiographic result at 6 months after the PED placement. Furthermore, the predictors of an incomplete occlusion were investigated in detail.Results: One hundred nine aneurysms locations were: C1 (9), C2 (30), C3 (15), C4 (53), and C5 (2) in the internal carotid artery segments. Perioperative morbidity, including the asymptomatic ones, occurred in 10 cases (10.6%). Among these 10 cases, the modified Rankin Scale (mRS) improved to preoperative mRS after 90 days in 9 cases except 1 case. On the other hand, no perioperative mortality was observed. The postoperative cranial nerve improvement rate was 84.4%, and 61.7% of patients had a complete occlusion in the follow-up angiography, 6 months after the PED placement. Predictive factors for an incomplete occlusion after the PED placement were the elderly aged 70 years or older (P-value = 0.0214), the elderly aged 75 years or older (P-value = 0.0009), and the use of anticoagulants (P-value = 0.0388) in an univariate analysis. Further, the multivariate analysis revealed that the elderly aged 75 years or older was a predictive factor of an incomplete occlusion in this study.Conclusion: We summarized the outcomes of the PED treatment at our single center. In this study, the elderly aged 75 years or older was a predictive factor of an incomplete occlusion after the PED placement.